PENINGKATAN MINAT BELAJAR PENDIDIKAN AGAMA ISLAM MELALUI PEMANFAATAN MEDIA PEMBELAJARAN BERBASIS ANDROID PADA PESERTA DIDIK KELAS X SMA NEGERI 1 KOLAKA - Syamsidar Syamsidar; Muhammad Akbar; Nurthahirah Umajjah (Universitas Sains Islam Al Mawaddah Warrahmah Kolaka, 2023)
This research aims to investigate whether there is or there is no improvement on students’ learning interest through the utilization of Android-based learning media (Andoromo) at X grade in SMA Negeri 1 Kolaka. Research problem addressed in this research is how is the utilization of android-based Islamic Education media can improve students’ learning interest at X grade of SMA Negeri 1 Kolaka. The research objective in this study is to find out how android-based Islamic Education media can improve students’ learning interest. Thereby, I n order to answer the research problem addressed in this research used Classroom Action Research (CAR) design with qualitative approach. The amount of sample in this research is 31 students. Technique of data collection in this research was by using questionnaire which distributed to the respondent and documentation. This research can be called success if 75% of the respondent give positive respond toward the questionnaire which was asked about android (andromo) based learning. The result of this research shows that there is an improvement on students’ learning interest when learning toward android based learning. This result proved by the result of percentage accumulation in I cycle which at 52% students gave positive respond and 48% students still gave negative respond. In cycle II, the were 85% students give positive respond or agree to the usage of android-based learning, and 15% students give negative respond to the usage of android (andromo)-based learning.